1998
DOI: 10.1007/s004770050013
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of transport of non-ergodic solute plumes in heterogeneous aquifers

Abstract: Transport of non-ergodic solute plumes by steady-state groundwater ow with a uniform mean velocity, l, were simulated with Monte Carlo approach in a two-dimensional heterogeneous and statistically isotropic aquifer whose transmissivity, T, is log-normally distributed with an exponential covariance. The ensemble averages of the second spatial moments of the plume about its center of mass, hS ii ti, and the plume centroid covariance, R ii t i 1Y 2, were simulated for the variance of Y log T, r 2 Y 0X1, 0.5 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
18
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 39 publications
7
18
0
Order By: Relevance
“…5) and Zhang and Lin (1998) found that their simulated X 22 are significantly higher than the first-order solution and are very close to the values derived using Corrsin's conjecture. Most recently, Dentz et al (2002) carried out numerical simulations of the temporal behavior of a passive solute in a saturated three-dimensional heterogeneous medium and their results are compared to the second-order perturbation theory expressions derived early by the same authors (Dentz et al 2000a, b).…”
Section: Introductionsupporting
confidence: 83%
See 4 more Smart Citations
“…5) and Zhang and Lin (1998) found that their simulated X 22 are significantly higher than the first-order solution and are very close to the values derived using Corrsin's conjecture. Most recently, Dentz et al (2002) carried out numerical simulations of the temporal behavior of a passive solute in a saturated three-dimensional heterogeneous medium and their results are compared to the second-order perturbation theory expressions derived early by the same authors (Dentz et al 2000a, b).…”
Section: Introductionsupporting
confidence: 83%
“…They (Fig. 3, Zhang and Lin 1998) showed that the simulated transverse centroid variance R 22 and thus the one-particle transverse variance X 22 are very sensitive to the value of e: the simulated R 22 increases as the value of e decreases. While the simulated Z 22 for all values of e they used are above the first-order theoretical curve, the simulated R 22 increases from below to above the first-order theoretical curve.…”
Section: Model Validationmentioning
confidence: 94%
See 3 more Smart Citations